EFFECT OF PROFITABILITY AND LIQUIDITY ON COMPANY VALUE - Shofi Hadyanti Kurnia; Irvan Yoga Pardistya (Jurnal Ilmu Manajemen Profitability, 2021)
This study aims to determine the effect of profitability and liquidity on firm value in food and beverage sub-sector manufacturing companies listed on the IDX for the 2015-2019 period. In this study using quantitative descriptive methods. The type of data in this research is secondary data. The data collection technique used was purposive sampling. The analysis method used is multiple linear regression analysis. The results showed that profitability had a significant positive effect on firm value. Meanwhile, liquidity has no effect on firm value.